SOME PSYCHOLOGICAL INTERVENTIONS ORIENTATED TOWARD ABSTINENCE IN ALCOHOL DEPENDENTS - García González, Raquel (Anales de Psicología / Annals of Psychology)
In this paper a brief synthesis of some psychological interventions applied to alcohol dependents is carried out. Some behavioural and cognitive techniques such as aversive techniques, training in incompatible behaviours and relapse prevention programmes pointed towards abstinence are revised. Some of the difficulties found in their application and some others aspects related to effectivity of treatments in this addictive behaviour are commented.